1999
DOI: 10.1108/07363769910277166
|View full text |Cite
|
Sign up to set email alerts
|

Chinese children as consumers: an analysis of their new product information sources

Abstract: The research reported here was a first attempt to determine where Chinese children as consumers learn information about new products and their attitudes toward different sources of information. Chinese children's usage of the mass media was also examined, as was the relationship between mass media usage and information sources. The findings show that Chinese children utilize a wide variety of information sources to learn about new products including parents, retail outlets, and the mass media, and surprisingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 24 publications
3
104
0
3
Order By: Relevance
“…Parents serve as role models and influence adolescents' purchase behavior directly (McNeal and Ji, 1999). Empirical data support the notion that parental support for healthy meals and nutrition skills have a positive association with adolescents' healthy food choices and healthy eating habits (Raiha et al, 2006;Young and Fors, 2001).…”
Section: Introductionmentioning
confidence: 66%
“…Parents serve as role models and influence adolescents' purchase behavior directly (McNeal and Ji, 1999). Empirical data support the notion that parental support for healthy meals and nutrition skills have a positive association with adolescents' healthy food choices and healthy eating habits (Raiha et al, 2006;Young and Fors, 2001).…”
Section: Introductionmentioning
confidence: 66%
“…Blackwell et al (2001:387) considers family communication about purchases as the key to children's consumer socialisation. When children need information on new products, the findings of a study by McNeal and Ji (1999) indicate that television and parents ranked the highest among Chinese children. Parents can use television advertisements in various ways as a means of communicating and educating their children in consumer matters.…”
Section: How Parents Use Television Advertisements For the Consumer Smentioning
confidence: 99%
“…Both advertising and editorial/ program content of the mass media provide children with knowledge and guidance in their consumer behavior development. McNeal and Ji (1999) found that Chinese children utilized a wide variety of information sources to learn about new products including parents, retail outlets, and the mass media, and that they considered television to be the most important. The researchers concluded that a new consumer generation is emerging in urban China that is more exposed to and more open to commercial sources.…”
Section: Children As Consumersmentioning
confidence: 99%
“…However, the study did not examine children's evaluation of credibility of information sources. Also, McNeal and Ji's (1999) study surveyed children in grades 4 to 6 only and thus unable to provide information about the development of shopping knowledge and perception of information sources with age. The study presented here remedies this limitation by extending the scope to cover children age six to 12 in urban China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation